Analysing trunk and arm motion in volleyball jump serve: a comparison of straight line and diagonal line techniques - Liu, L.; Chen, Z.; Peng, H.-T.; Zhao, D.; Tan, Z. (Sports Biomechanics, 2025)
This study aimed to clarify the disparities in trunk rotation and attack arm movement and their effect on hand kinematics adjustments between straight-line (SL) and diagonal-line (DL) volleyball jump serves. Thirteen male professional volleyball players (age 21.53 ± 5.39 years, height 1.95 ± 0.06 m, body mass 86.48 ± 11.63 kg, experience 8.61 ± 3.47 years) performed SL and DL jump serve, with three-dimensional coordinate data captured using a motion capture system (200 hz). Paired t-test and statistical parametric mapping examined kinematic differences between the two serving directions. At ball contact (BC), the speed of the attack arm hand was significantly faster in DL (16.99 ± 1.36 m/s) compared to SL (16.37 ± 1.53 m/s), whereas the face angle was significantly smaller in DL (1.98 ± 11.75°) than in SL (17.60 ± 17.98°). Forward rotation angles of the pelvic and upper torso at BC were significantly greater in DL (28.47 ± 10.89°; 21.30 ± 10.25°) than in SL (18.27 ± 12.46°; 9.09 ± 14.41°). During the arm swing phase, the pelvic`s forward rotation angles in DL were significantly greater than in SL at 42-72% spiking motion, and the upper torso`s angles were significantly greater at 49-58% spiking motion. These findings underscore the importance of adjusting pelvic and upper torso rotations to control the hand`s face angle when serving in the diagonal line.